(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Production of cement generates large quantity of carbon dioxide nearly 6 to 7 in percentage of total 9.795 Gigatonnes of CO2 emission. There is a need to extend sustainable substitute to Portland cement utilizing the industrial by-products such as fly ash, ground granulated blast furnace slag which are Pozzolanic in nature. An experimental analysis on the Compressive, flexural and split tensile behavior of Geopolymer mortar as well as Conventional mortar reinforced with rectangular welded with varying number of mesh. Specimen are casted using cement mortar and Geopolymer mortar separately. The specimens are tested under flexural, compressive and Split tensile loading. 750 x125 x 35 in mm size of the mould is prepared for flexural specimens. Samples are prepared like panels for flexural testing and cylinders for Compressive and Split tensile testing. The sample specimens from the mould will be demoulded and kept for curing. Then the samples tested on UTM and CTM and observations were recorded to draw results and conclusions.